Q. 114.5( 66 Votes )

Solve</span

Answer :






(a + b + x)x = –ab


ax + bx + x2 = –ab


x2 + ax + bx + ab = 0
x(x + a) + b(x + a) = 0


(x + a)(x + b) = 0


x = –a or x = –b


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses